Carbonic anhydrases in the cell wall and plasma membrane of Arabidopsis thaliana are required for optimal plant growth on low CO2 - Weerasooriya, Hiruni N.; Longstreth, David J.; DiMario, Robert J.; Rosati, Viviana C.; Cassel, Brittany A.; Moroney, James V. (Frontiers in Molecular Biosciences, 2024)
Plants have many genes encoding both alpha and beta type carbonic anhydrases. Individual carbonic anhydrases are localized to specific compartments within the plant cell. In this study, we investigate the roles of αCA2 and βCA4.1 in the growth of the plant Arabidopsis thaliana under different CO2 regimes. We found that plants missing both αCA2 and βCA4 grew poorly at 200 μL L -1 CO2 but normally at 400 and 1000 μL L -1 CO2. Methods: Here, we identified the intracellular location of αCA2 and βCA4.1 by linking the coding region of each gene to a fluorescent tag. Tissue expression was determined by investigating GUS expression driven by the αCA2 and βCA4.1 promoters. Finally, the role of these proteins in plant growth and photosynthesis was tested in plants with T-DNA insertions in the αCA2 and βCA4 genes. Results: Fluorescently tagged proteins showed that αCA2 is localized to the cell wall and βCA4.1 to the plasma membrane in plant leaves. Both proteins were expressed in roots and shoots. Plants missing either αCA2 or βCA4 did not show any growth defects under the conditions tested in this study. However, if both αCA2 and βCA4 were disrupted, plants had a significantly smaller aboveground fresh weight and rosette area than Wild Type (WT) plants when grown at 200 μL L -1 CO2 but not at 400 and 1000 μL L -1 CO2. Growth of the double mutant plants at 200 μL L -1 CO2 was restored if either αCA2 or βCA4.1 was transformed back into the double mutant plants. Discussion: Both the cell wall and plasma membrane CAs, αCA2 and βCA4.1 had to be knocked down to produce an effect on Arabidopsis growth and only when grown in a CO2 concentration that was significantly below ambient. This indicates that αCA2 and βCA4.1 have overlapping functions since the growth of lines where only one of these CAs was knocked down was indistinguishable from WT growth. The growth results and cellular locations of the two CAs suggest that together, αCA2 and βCA4.1 play an important role in the delivery of CO2 and HCO3 -to the plant cell.